Option of the Optical-mechanical Positioning of the Sensor and Sample in the Magnetometer. Determination of Magnetic Susceptibility of Powders and particles - Sandulyak, Alexander; Sandulyak, Anna; Kiselev, Dmitriy; Polismakova, Maria; Bulut, Hasan (E D P Sciences, 2018)
In Faraday's magnetometer it is recommended to apply remotely the located poles hemispheres. In this case (and similar cases) there is a need for expeditious and exact positioning of the measuring sensor (Hall) and the studied sample for obtaining the most authentic characteristics of induction and its gradient, identification and use of a zone of stability. This problem is solved by the corresponding optical-mechanical system of positioning. It consists of the laser modules promoting aim positioning, the Web camera promoting final positioning. On the received concentration dependences of magnetic susceptibility of powder samples existence of limited line sections is confirmed that gives the chance to define susceptibility of particles. The critical relation to use for the similar purposes of samples (disperse) in the form of colloids and suspensions expresses.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: By-Channel Magnetization; Model